Evaluation of downy mildew resistance in the cucumber inbred lines - Khanobdee, Chanulak; Charoenwattana, Piyavadee; Samipak, Sompid (RMUTSB ACADEMIC JOURNAL, 2016)
Downy mildew, a foliar disease caused by the oomycete Pseudoperonospora cubensis (Berk. and Curt.) Rostov. is one of the most destructive diseases of cucumber (Cucumis sativus L.) in tropical and temperate areas of the world. Resistant cucumber cultivars in Thailand had the sufficient resistance to grow a successful crop without the use of fungicides. The objective of this study was to identify new sources of the resistance and the susceptible to downy mildew of inbred lines from the RMUTL and NSTDA cooperating project, elite cultivars, and breeding lines of cucumber. Eight inbred lines were evaluated in Lampang province, during 2012 to 2014 under the natural field and the nursery epidemics. To describe genetic homozygous, eight inbred lines were constructed using 70 pooled DNA and single plant DNA of simple sequence repeats (SSR) markers.